PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS ETNOSAINS PADA KONSEP LARUTAN ELEKTROLIT DAN NONELEKTROLIT (Universitas Negeri Semarang, 2021)
Chemical learning lays a major emphasis on learning concepts and formulas. While in daily life, the application is less applied so that learning becomes less meaningful. Ethnoscience learning can be applied with the help of teaching materials in the form of Student Worksheets so learners can connect existing knowledge, such as culture or native community knowledge with scientific knowledge. The study aims to develop the learner's worksheet ethnoscience-based on one of the original knowledge of the communities, the use of fresh coconut water associated with the material's electrolyte and nonelectrolyte. This research is a research development with the method of Analysis, Design, Development Implementation, Evaluation (ADDIE). Data collection techniques using needs analysis in the form of library and field tests (interviews and questionnaires). Validity test using Content Validity Ratio (CVR) with 11 Validator consisting of lecturer and chemistry teacher, and the student response questionnaire. Research shows that the developed LKPD was qualified and valid to be used with a CVR 0.82 â€“ 1.00 that shows a CVR 0.59. Students also have a proud attitude, responsibility, and awareness to preserve the culture of fresh coconut water consuming.Â